Evolving perspectives on speech perception assessment in adults with cochlear implants: Are we using the right tests? - Shafiro, Valeriy; Moberly, Aaron C.; Pisoni, David B.; Tamati, Terrin N. (Frontiers in Neuroscience, 2025)
From the pioneering days of cochlear implants (CIs) more than half a century ago until the present time, speech perception outcomes remain a broadly recognized benchmark of CI success. However, speech test scores alone do not directly map onto individual patients’ aural communication needs. Rather, speech tests provide a relatively time-efficient way to assess specific aspects of everyday speech processing abilities. We review how speech perception testing has evolved in the United States of America since the early days of CIs and critically examine its current clinical roles: (1) establishing CI candidacy, (2) measuring benefit post-CI, and (3) pinpointing specific perceptual deficits to guide counseling, rehabilitation, or programming changes. We further consider: (a) factors that have driven changes in how speech perception has been evaluated over time, (b) approaches to selecting outcome measures of speech perception and interpretation of outcomes, (c) the role that speech perception plays in the assessment of overall CI benefit and individualized rehabilitation, and (d) how test selection and conditions can influence CI care. We argue that conventional speech perception tests provide only a partial view of CI outcomes and call for more comprehensive, ecologically meaningful assessment approaches. We conclude with recommendations for selecting outcome measures that better reflect real-world communication demands and guide patient-centered care for adult CI users.